HLA-A gene knockout using CRISPR/Cas9 system toward overcoming transplantation concerns - Farshid Amiri; Maryam Ranjbar; Mohammad Pirouzfar; Marjan Nourigorji; Mehdi Dianatpour (Egyptian Journal of Medical Human Genetics, 2021)
Abstract Background The treatment of many cancers and genetic diseases relies on novel engraftment approaches such as cell therapy and hematopoietic stem cell transplantation (HSCT). However, these methods are hindered by the alloreactive immune responses triggered by incompatible human leukocyte antigen (HLA) molecules. A successful HSCT procedure requires the eradication of donor and recipient HLA alloimmunization. Eliminating HLA-A gene expression using clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 nuclease (CRISPR/Cas9) could be a great approach to increase the possibility of a successful HSCT through extending pool of unrelated donors. Results Our dual gRNA approach introduced a large deletion in the HLA-A gene. Among 22 single-cloned cells, two clones (9.09%) and 11 clones (50%) received homozygous and heterozygous large deletions, respectively. Finally, the real-time PCR results also revealed that HLA-A gene expression was diminished significantly. Conclusion The results suggested that CRISPR/Cas9 could be used as an efficient technique to introduce HLA-A gene knockout; thus, it can considerably lessen the burden of finding a fully matched donor by lowering the alleles required for a successful HSCT.